The Assessment of Ecosystem Services in Urban Areas - Dubosaitė-Lepeškevičė, Roberta; Balvočiūtė, Rasa (Socialiniai tyrimai, 2018)
This article presents the methods for assessing the ecosystem services in foreign countries, the metaanalysis of the literature is conducted considering what methods of assessment of natural ecosystems are applied, as well as the advantages and disadvantages of applied assessment methods are analysed. It is aimed to find the method or the system of methods assessing the ecosystem services which are the most suitable to assess the services provided by ecosystem in urban areas.The rational and balanced use of ecosystem services is very important for their socio-economic assessment, the protection of biodiversity in cities in order to ensure the recreational, cultural, economic, social, sanitary, hygienic and other needs of society. According to the principle of sustainable development, the economic and social development of the country has to be oriented so that the meeting today’s needs would not diminish the possibilities to satisfy the needs of future generations, to account for resource constraints, with a view to sustainable use and conservation of resources. Such data are essential to form the policy of natural resource consumption through the management of national resources. The public is more aware of the aesthetic and protective functions of natural ecosystem, but they do not have sufficient knowledge of their economic and social value. Although foreign literature provides a large number of studies in this sphere, only individual methods for assessing the ecosystem services are analyzed in Lithuania. Research in the evaluation of the ecosystem services in Lithuania has not been developed. When it is not possible to quantify the supply with demand for ecosystem services, it is more difficult to prove the real economic risks that arise. Answers to these issues are necessary not only for scientists but also for managers in deciding on the adaptation of limited natural resources for social needs and preservation for future generations. To assess the ecosystem services in urban areas, which are described as ecosystem conditions and processes contributing to human quality of life and important for day-to-day decisions at the political, economic and environmental levels, there is a need for an economic and social assessment system that helps to determine the value of ecosystem services. The value of ecosystem services in most countries of the world is underestimated and incorporated into decision-making. It is important to analyze the theoretical principles of assessing the ecosystem services to develop the economic and social model for the future assessment of the ecosystem services.Analytical methods are more essential in comparing the use of ecosystems than establishing the absolute ecosystem values. Selection methods are used for assessing ecosystem services: market, travel costs, hedonistic. Priority methods: joint analysis, contingent assessment are used as well. Cost-based avoidance methods are used when ecosystem services are valued according to costs incurred as a result of the loss of the ecosystem service or the costs of transferring or replacing the service. The new method for evaluating ecosystem services is the method of deliberative monetary valuation. The multi-criteria assessment method allows to conduct the simultaneous evaluation of several contradictory criteria, which is especially relevant for environmental decision-making. For socio-economic evaluation of ecosystem services, researchers apply a cost-benefit analysis method that is most often used to evaluate public sector investment projects. These projects are generally financially unprofitable, but aim at identifying the socioeconomic value they create. The value-for-consumption and non-use value of ecosystems in the overall economic value structure can be determined by consumer valuation, contingent or hedonistic price methods. The valuation of non-market (non-market flows or assets) is, in essence, an indication of the environmental performance of aggregates rather than a specific expression of the market price of a financial transaction. For this purpose, the subjective, hypothetical value and price determination and justification methodology, the subjective approach based on the value of indirect use or disclosed preferential methods are used to define the value and determine the value. In many cases, ecosystem services are not marketed and do not have market prices, but their economic value or market value cannot be assumed to be zero. In cases where ecosystems do not have a market price (because there is no market), but an individual agrees (is willing) to pay for the opportunity to use it or receive compensation for not using it, the economic value of the good would be related to the amount of the price paid by the consumer. The benefits of urban ecosystems are indirect, therefore, it is often difficult to assess it in monetary terms. However, it is necessary to compare the benefits and costs of this ecosystem resource. It is suggested that different ecosystem services provided in the cities are identified by using different assessment methods appropriate to different ecosystem types. Selection methods based on human behavior and choice are used in cases where interrogators may experience different effects of the provided ecosystem service. These are market price, travel costs, hedonistic, deliberative monetary valuation methods. The preferred methods of disclosure-contingent assessment, choise experiment methods are used to determine the value of non-use provided by all three types of ecosystem services. The value of non-use of ecosystem services is the value of preserving and retaining biodiversity for future generations. The set value helps to prevent loss of change. The most recent method for evaluating ecosystem services – the method of deliberative monetary valuation – is more appropriate to be regarded not as the main but as an additional assessment method. The multicriteria method allows to conduct simultaneous evaluation on the basis of several contradictory criteria, which is especially relevant for national policies in environmental issues. The cost-benefit analysis method is most often used in evaluating public sector investment projects. These projects are generally financially unprofitable, but aim at identifying the socioeconomic value they generate.In determining the value of providing ecosystem services in cities, it is important to choose the right method or system. The diversity of ecosystem services and their functions suggests that it is necessary to integrate assessment methods in such a way as to enable them to reflect the benefits of these services for the public not only at present, but also preserving the ecosystem for future generations. All methods have the advantages and the disadvantages, only by combining them we can have rational assessment of natural ecosystem services. In the evaluation of the services provided by the type of ecosystem in the city, it is suggested to use cost benefit analysis and conjoint analysis methods. The contingent assessment method should be used to assess cultural and regulatory services. An appropriate regulatory type of ecosystem services is evaluated using both multicriterion and choise experment methods, integrating the contingent method with the travel cost method when assessing cultural ecosystem services. In order to incorporate society into decision-making, additional methods of a deliberative monetary valuation and expert evaluation are needed.
Keywords: ecosystem; ecosystem services; assessment methods; urban areas